The Molecular Structure and Chromatographic Parameters of Calix[4]аrеnehydroxymethylphosphonic Acids - Kalchenko, O.I.; Cherenok, S.O.; Rozhenko, O.B.; Yushchenko, O.A.; Kalchenko, V.I. (Журнал органічної та фармацевтичної хімії, 2012)
The basic chromatographic characteristics (retention time, tR, capacity factors, k’, and coeffi cients of asymmetry peaks, KS) of the number of biologically signifi cant calix[4]аrenehydroxymethylphosphonic acids and their sodium salts have been obtained in a reversed-phase high-performance liquid chromatography (RP HPLC) on Zorbax CN. The structure of calix[4]аrenehydroxymethylphosphonic acids have been studied by the molecular modeling method (TURBOMOLE program). The relationship between the structure and chromatographic characteristics of the calix[4]аrenes, as well as their sorption mechanism on the column surface have been discussed. Основні хроматографічні характеристики (часи утримання tR коефіцієнти ємкості к', коефіцієнти асиметрії піків КS) низки біологічно значимих калікс[4]аренгідроксиметилфосфонових кислот та їх натрієвих солей були визначені методом обернено-фазної високоефективної рідинної хроматографії (ОФ ВЕРХ) при застосуванні хроматографічної насадки Zorbax CN. Будову калікс[4]аренгідроксиметилфосфонових кислот було досліджено методом молекулярного моделювання (програмний пакет TURBOMOLE). Обговорено взаємозв'язок між будовою, хроматографічною поведінкою та механізмом сорбції каліксаренів поверхнею хроматографічної насадки. Основные хроматографические характеристики (времена удерживания коэффициенты емкости к', коэффициенты асимметрии пиков КS) серии биологически значимых каликс[4]аренгидроксиметилфосфоновых кислот и их натриевых солей определены методом обращенно-фазной высокоэффективной жидкостной хроматографии (ОФ ВЭЖХ) при использовании хроматографической насадки Zorbax CN. Строение каликс[4]аренгидроксиметилфосфоновых кислот исследовано методом молекулярного моделирования (программный пакет TURBOMOLE). Обсуждена взаимосвязь между строением и хроматографическим поведением и механизмом сорбции каликсаренов поверхностью хроматографической насадки.